Prevalence of Eating Disorders and Their Association with Psychosocial Wellbeing Among Adults in an Urban Area of Tamil Nadu, India - Gowtham S; Anantha Eashwar VM; Ilaval, Ilam; Sekhar, Monica Albert; Sushmitha G; Devi R, Swathika (National Journal of Community Medicine, 2025)
Background: Eating disorders are caused by the dynamic interaction of biological, psychological and sociocultural factors that affect physical and psychological well-being of humans. It leads to abnormal behavior in eating habits and excessive concern with body appearance and shape. Methodology: A cross-sectional study was conducted among 350 people in urban field practice area of tertiary care hospital, Chengalpattu district by simple random sampling. Data was collected using standard questionnaires and analysed using SPSS v25. Analytical tests like Chi-square and odds ratios were used to find association between the presence of eating disorders following which enter method of logistic regression was done. Results: Out of 350 participants prevalence of eating disorder was found to be 81(23.1%). Gender (AOR-6.15, 95%CI- 2.31-16.34), Occupations (AOR-2.49, 95%CI-1.13-5.48), Diet (AOR-6.06, 95%CI-2.01-18.30), family history of mental health problems (AOR-4.71, 95%CI-1.42-15.54), BMI and poor wellbeing (AOR-2.82, 95%CI-1.32-6.01) were statistically significant. Conclusion: The risk of eating disorders was high among the female participants. Exercise, Body image perception, and family history of mental health problems are also associated with eating disorder. These findings show the need for targeted awareness programs and mental health interventions, particularly among high-risk groups such as females and individuals with poor well-being, to effectively address and prevent eating disorders.